(untitled) (Research, Society and Development, 2024)
With its core values of training based on a humanistic vision, person-centered care, population management skills, and longitudinal monitoring in work with different life cycles, family and community medicine is a medical specialty responsible for addressing suffering and understanding the impact of social determinants on the behavior of interpersonal and family relationships, associated with manifestations and worsening of pathologies, in the different transition phases of life. Within this approach, the specialty includes in its training the development of communication skills that strengthen issues such as empathy and compassion in the essence of daily medical practice, using family instruments to bring families closer to the decision-making process and patient care in a horizontal and participatory manner. Thus, family and community medicine developed as a strategic specialty for work inserted in pain relief, comprehensive individual and family care, as well as in the longitudinal monitoring of life-threatening diseases and people in the finite phase of life, inserted in the context of palliative care, from primary care to care in a hospital environment. Based on the literature, this article aims to discuss the opportunities of the biopsychosocial vision of family medicine from the perspective of needs and potential for expanding palliative care.